Novel Anti-Cytokine Strategies for Prevention and Treatment of Respiratory Allergic Diseases - Gubernatorova, Ekaterina O.; Namakanova, Olga A.; Gorshkova, Ekaterina. A.; Medvedovskaya, Alexandra D.; Nedospasov, Sergei A.; Drutskaya, Marina S. (Frontiers in Immunology, 2021)
Asthma is a heterogeneous inflammatory disease characterized by airflow obstruction, wheezing, eosinophilia and neutrophilia of the airways. Identification of distinct inflammatory patterns characteristic of asthma endotypes led to the development of novel therapeutic approaches. Cytokine or cytokine receptor targeting by therapeutic antibodies, such as anti-IL-4 and anti-IL-5, is now approved for severe asthma treatment. However, the complexity of cytokine networks in asthma should not be underestimated. Inhibition of one pro-inflammatory cytokine may lead to perturbed expression of another pro-inflammatory cytokine. Without understanding of the underlying mechanisms and defining the molecular predictors it may be difficult to control cytokine release that accompanies certain disease manifestations. Accumulating evidence suggests that in some cases a combined pharmacological inhibition of pathogenic cytokines, such as simultaneous blockade of IL-4 and IL-13 signaling, or blockade of upstream cytokines, such as TSLP, are more effective than single cytokine targeting. IL-6 and TNF are the important inflammatory mediators in the pathogenesis of asthma. Based on our data in mice we propose that combined pharmacological inhibition of TNF and IL-6 during asthma may be more efficient as compared to individual neutralization of these cytokines. Here we summarize recent findings in the field of anti-cytokine therapy of asthma and discuss immunological mechanisms by which simultaneous targeting of multiple cytokines as opposed to targeting of a single cytokine may improve disease outcomes.